(untitled) (Sains Humanika, 2016)
Specification writing is an important aspect of architectural curriculum; as failure of the architect to write an effective specification in educational training and construction-practice may lead to unpalatable factors. This study explored couple of methods employed in the teaching, learning and assessment of specification writing students in architecture department, Covenant University, South-West Nigeria, with a view to identifying the most effective method within the group dynamics. The methodology adopted for this study involved the interview of M.Sc. II architecture students and adoption of two (2) basic pedagogic methods namely Traditional and Revolutionary during class sessions. The qualities were evaluated and assessed through the outcome of students’ assignments, standard performance tests and examinations results, and documentations in brainstorming-interactive class sessions. It was found that there were significant differences between the performance scores of students using diverse pedagogic methods. It recommended that further research capable of bridging education and construction- practice in synergy.Â